2012
DOI: 10.1364/oe.20.019355
|View full text |Cite
|
Sign up to set email alerts
|

Solitons in parity-time symmetric potentials with spatially modulated nonlocal nonlinearity

Abstract: We study the solitons in parity-time symmetric potential in the medium with spatially modulated nonlocal nonlinearity. It is found that the coefficient of the spatially modulated nonlinearity and the degree of the uniform nonlocality can profoundly affect the stability of solitons. There exist stable solitons in low-power region, and unstable solitons in high-power region. In the unstable cases, the solitons exhibit jump from the original site to the next one, and they can continue the motion into the other la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…In Ref. [118] the effect of spatially modulated nonlocal nonlinearity has been addressed. It was shown that there exist regions where gap solitons and defect modes are stable, and that the degree of nonlocality affects these regions drastically.…”
Section: Generalized Nonlinear Potentialsmentioning
confidence: 99%
“…In Ref. [118] the effect of spatially modulated nonlocal nonlinearity has been addressed. It was shown that there exist regions where gap solitons and defect modes are stable, and that the degree of nonlocality affects these regions drastically.…”
Section: Generalized Nonlinear Potentialsmentioning
confidence: 99%
“…Spatiotemporal solitons [also called "light bullets" (LBs)] [10][11][12] exist due to the result of the simultaneous balance of diffraction and group velocity dispersion (GVD) by the transverse self-focusing and nonlinear phase modulation in the longitudinal direction, respectively. Recently, the propagation of solitons in − symmetric potentials was presently attracting a great interest both from the theoretical and from the applicative point of view [13][14][15][16][17][18][19][20][21]. The − symmetry has been applied into linear and nonlinear lattices [13], double-channel waveguides [14], and nonlocal nonlinearity [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the propagation of solitons in − symmetric potentials was presently attracting a great interest both from the theoretical and from the applicative point of view [13][14][15][16][17][18][19][20][21]. The − symmetry has been applied into linear and nonlinear lattices [13], double-channel waveguides [14], and nonlocal nonlinearity [15]. Stable bright spatial solitons in defocusing Kerr media with − symmetric potentials have been studied [16].…”
Section: Introductionmentioning
confidence: 99%
“…Bright solitons can also exist in PT-symmetric potentials with nonlocal nonlinearity [27][28][29][30][31][32]. Nonlocal fundamental and dipole defect solitons can exist in different gaps in PT-symmetric optical lattices with focusing nonlinearity [27].…”
Section: Introductionmentioning
confidence: 99%
“…Nonlocal fundamental and dipole defect solitons can exist in different gaps in PT-symmetric optical lattices with focusing nonlinearity [27]. Bright nonlocal fundamental solitons in PT-symmetric optical lattices with spatially modulated nonlinearity were discussed [28], with different of the coefficients of the real nonlinear modulated function, the stable domains will be different. The degree of nonlocality can affect the stability of fundamental solitons in the dual-periodic PT-symmetric optical lattices [29].…”
Section: Introductionmentioning
confidence: 99%